Ruminants´production within agroforestry systems in rural Rwanda - Olsson, Pernilla (2012)

(untitled)
Intercropping involving trees is called agroforestry and makes it possible to get higher production for every area unit. The trees can function as food, fodder, fuel, medicine; prevent mark erosion and much more. Agroforestry can also be combined with animal husbandry. The aim of this study was to document the animal production systems used by rural small-scale farmers maintaining ruminants and using agroforestry in the northern province of Rwanda. The farmers using agroforestry is expected to have higher milk yield than average due to homegrown protein. The method used during the study was semi-structural interviews with booth open and closed questions. In order to get in contact with farmers that matched the criteria; small-scaled rural farmers with ruminants and using agroforestry, the “Vi Agroforestry Programme” (Vi-Life) in Kigali were contacted and the staff worked as supervisors, translators and contact with the farmers throughout the study. During the study nine individual farmers, two cooperatives breeding sheep and one group interview were conducted. In total twelve interviews were made with 32 farmers. Of these farmers 28 reported that they had ruminants. The majority of the farmers had cows with milk production being the primary purpose, while the main purpose with small ruminants was compost to use as fertilizer at the fields. The biggest benefits as a result of the milk production and the compost were a daily income and higher crop yield respectively. The majority of the individually interviewed farmers housing cows had a larger milk yield than the East Africa community average of seven liters per day and cow.